Pembelajaran Mendalam (Deep Learning) Perspektif Imam Al-Ghazali Dan Michael Fullan - Elviana India Sinta Dewi; Suwendi Suwendi; Abdul Mukti (Jayapangus Press, 2026)
Deep learning is a central issue in contemporary education because it emphasizes meaningful understanding, reflection, and the relevance of learning materials to real life. However, the integration of modern pedagogical approaches and spiritual values has rarely been examined systematically. This study analyzes and compares the concept of deep learning according to Imam Al-Ghazali and Michael Fullan to identify conceptual intersections and potential synthesis. The method employed is a systematic literature review with a comparative approach, utilizing primary sources from Imam Al-Ghazali (Ayyuhal Walad) and Michael Fullan (Deep Learning: Engage the World, Change the World), as well as relevant scholarly literature from the past ten years. The analysis was conducted thematically and comparatively. The findings show that Al-Ghazali emphasizes character formation, purification of the soul, and spiritual orientation, whereas Fullan focuses on developing 21st-century competencies through the 6C framework. The synthesis of these two perspectives gives rise to the concept of “authentic learning,” which integrates spiritual dimensions and global competencies. This concept has the potential to enrich holistic educational practices in Indonesia, particularly in building a generation with strong character and global competitiveness.